UZBEKISTAN SCIENTISTS WHO HAVE CONTRIBUTED TO THE FIELD OF SYNTAX (International journal of artificial intelligence, 2025)
This article analyzes the leading scholars who contributed to the development of the section of syntax in Uzbek linguistics and their scientific heritage. Syntax plays an important role in the study of the grammatical structure of the Uzbek language. This study provides information about Uzbek linguists who have covered issues of syntax, their research areas, and their main scientific works.